Instituto Nacional de Seguro Social (INSS) : uma análise da "modernização" da previdência social brasileira - Vasconcelos Junior, Jorge Og de (2017)
This dissertation is about the "modernization" initiatives of Brazilian social security, even before its institutionalization in the 1920s until the New Model of Management Project (PNMG) of 2002. Thus, it was aimed to analyze the repercussions that the project of "Modernization" of the 2002 INSS management brought to the work processes and recognition of social rights in the Institution with a view to providing the subsidies for future studies and reform actions of the current model. The research was guided by the method of historical and dialectical materialist investigation and exposition because it understood that it allows to unveil the real in its most diverse contradictions. Based on the use of the mixed approach, to analyze the information collected and from the bibliographic review and documentary analysis, the content analysis technique was used (BARDIN, 2009), organized around three stages: pre-analysis, The exploitation of the material and the treatment of results. Thus, the results show that until its institutionalization, politics was managed exclusively by its workers and constituted the first forms of class organization in Brazil. With the later co-participation of the State and the gradual minimization of workers' participation in the management of Brazilian social security, managerial problems intensified, taking this social policy to the abyss of bureaucracy that is still up to date. Since the 1920s, dozens of initiatives have been the conservative modernization of the social security system, but all of them are very similar in their superficiality to the emergency solutions found for such structural problems. Therefore, it is concluded that it is still possible to advance in effective management reforms in the INSS, as in the points referring to the greater participation of the users of the policy in the social control and planning of the same, reversing the jump in the number of complaints accumulated in the Ombudsman's Office that is Revealing the tensions in the user x INSS relation; In the rationalization of the occupation of management positions; And the (re) structuring of the Social Security Career. Finally, the expectation is that this study contributes to the debate of this important and fundamental issue that conflicts with Brazilian society.